Novel Germline BRCA1 and BRCA2 Mutations in Turkish Women with Breast and/or Ovarian Cancer and Their Relatives - Egeli, Unal; Cecener, Gulsah; Tunca, Berrin; Tasdelen, Ismet (Cancer investigation, 2006)
BRCA1 and BRCA2 gene mutations in patients with breast and/or ovarian cancer have been not characterized in the Turkish population until now. A total of 87 female subjects from two sets of families (38 families total) provided blood samples from which DNA was extracted. All coding exons of the BRCA1 and BRCA2 genes were screened for mutations with heteroduplex analysis and sequencing. Fourteen of the families (49 subjects comprising 17 patients and 32 unaffected relatives) had at least 2 women affected by breast and/or ovarian cancer. The other 24 families (38 subjects unaffected by breast and/or ovarian cancer) also had a history of these 2 forms of cancer. Six different sequence variants were detected: one previously described truncating mutation (5382insC) and one novel polymorphism (3663C→A) in BRCA1, and 2 novel truncating mutations (9329insC and 9934insG), one novel intronic polymorphism 7069+41(TTTT→AAAG), and one previously reported global polymorphism (1093A→C) in BRCA2. BRCAPRO software was used for analysis, and the results showed that the level of risk for both breast and ovarian cancer increased with age in women who carried the mutation. In conclusion, these findings contribute significantly to what currently is known about the types and impact of germline BRCA1 and BRCA2 mutations in Turkish women.